ANALISIS KOMPONEN KONDISI FISIK DOMINAN DALAM CABANG OLAHRAGA TARUNG DERAJAT - NOVIATMOKO, FEBRI (Jurnal Kesehatan Olahraga, 2016)
Tarung Derajat is aggressive and dynamic martial arts on the form of movement a blow, rebutter, beating, locking, and evasion. The physical condition has affected the performance of athletes when they played. Where tarung derajat is a martial sports with full body contactcategorythat when in the game, the athletes need a maximum physical condition to follow suit. The purpose of this study is to find the components of the most dominant of the physical condition that needed in sport branch tarung derajat. In this study, the data were drawn is taken from secondary data.Secondary data usually from documentation or datareports that has been available. So the data iscollected fromphysical coach of tarung derajatEast Java. Based on the study that has been done, obtained the conclusion that the power of the muscular stomach of man60 wasgood category with 10 athletes, on average 52.6 was medium category.The power of the muscular stomach of woman 100 was medium category with 5 athletes, the flattened42,6 was medium category. Togok flexibility ofman was 50enough category with 10 athletes, the average 14,45 was enoughcategory. Togok flexibility of woman 60 was lesscategory by 5 athletes, the average 14,48 was lesscategory.Endurance the arm muscles of man 60 was goodcategory with 10 athletes, the average 54.5 was goodcategory.Endurance the arm muscles of woman equal to 100% was good category with 5 athletes, the average 58,4 was goodcategory.Endurance the muscular stomach of man 70% was very good category with 10 athletes, the average 60,7 wasvery good category.Endurance the muscular stomach of woman 100 was very good category with 5 athletes, the average 55,6 was very goodcategory. The speed of man 60 was good category with 10 athletes, the average 4,37 seconds was medium category. The speed of woman 80 was very good category with 5 athletes, the average 4,46 seconds was very goodcategory. The agility of man 40was very goodcategory and 40 was good category with 10 athletes, the flattened 12,34 seconds was goodcategory. The agility of woman 60 was very goodcategory with 5 athletes, the flattened 12,79 seconds was goodcategory. Vo2 max of man 60 was medium category with 10 athletes, the average 53,61 wasmedium category. TestVo2 max of woman 60 was good category with 10 athletes, the average 51,59 was goodcategory. So it can be concluded that there are five aspects of physical condition that is dominant in the sports tarung derajat.They are the endurance of the muscular stomach, agility,the power of the muscular stomach, the endurance of the arm muscles, and the speed that supporting the success of athletes to following the championship and there are two components of physical condition that still to require improvement namely togok flexibility and Vo2 Max. Keywords : Physical condition, Tarung derajat